2005
DOI: 10.1111/j.1939-1676.2005.tb02701.x
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Congenital Extrahepatic Portosystemic Shunts in Cairn Terriers

Abstract: The pathogenesis of congenital portosystemic shunt (CPSS) in dogs still is incompletely understood. In Irish Wolfhounds and Yorkshire Terriers, CPSS is reported to be hereditary. The aim of this study was to investigate a possible genetic basis and the mode of inheritance of CPSS in Cairn Terriers. Between July 1990 and July 2001, 6-week-old pups of the Dutch Cairn Terrier population were screened by measuring venous ammonia concentrations and in the presence of hyperammonemia by ultrasonography, autopsy, port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 14 publications
1
32
1
Order By: Relevance
“…Although the genetic basis of CPSS in dogs is not clear yet, many authors have demonstrated that congenital shunts are more frequently diagnosed in purebred dogs and that a number of breeds are predisposed to it (Hunt 2004; Tobias 2003), which indicates an inherited basis for this disease (Meyer and Rothuizen 1991; van Straten et al 2005). An equal frequency of affected males and females was generally reported (Hunt 2004; van Straten et al 2005). In addition, EHPSS and IHPSS were very rarely seen in the same breed (Hunt 2004; Krotscheck et al 2007; Martin 1993; Tobias and Rohrbach 2003; Vulgamott 1985; Winkler et al 2003).…”
Section: Congenital Portosystemic Shunts and Associated Liver Dysfuncmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the genetic basis of CPSS in dogs is not clear yet, many authors have demonstrated that congenital shunts are more frequently diagnosed in purebred dogs and that a number of breeds are predisposed to it (Hunt 2004; Tobias 2003), which indicates an inherited basis for this disease (Meyer and Rothuizen 1991; van Straten et al 2005). An equal frequency of affected males and females was generally reported (Hunt 2004; van Straten et al 2005). In addition, EHPSS and IHPSS were very rarely seen in the same breed (Hunt 2004; Krotscheck et al 2007; Martin 1993; Tobias and Rohrbach 2003; Vulgamott 1985; Winkler et al 2003).…”
Section: Congenital Portosystemic Shunts and Associated Liver Dysfuncmentioning
confidence: 99%
“…Extrahepatic shunts occur in small dog breeds with a predisposition in Cairn terriers (van Straten et al 2005), Yorkshire terriers (Tobias 2003; Tobias and Rohrbach 2003), Jack Russell terriers (Hunt 2004), Dachshunds (van den Ingh et al 1995), miniature schnauzers, Havanese, Dandie Dinmont terriers (Tobias and Rohrbach 2003), and Maltese (Tisdall et al 1994). …”
Section: Canine Extrahepatic Portosystemic Shuntmentioning
confidence: 99%
“…CPSS was suspected upon clinical symptoms and increased basal plasma ammonia concentrations as previously described [30]. The diagnosis and localization of the CPSS (IHPSS or EHPSS) was made by ultrasonography and confirmed during surgery.…”
Section: Methodsmentioning
confidence: 99%
“…This occurs via an intrahepatic (IHPSS) or an extrahepatic portosystemic shunt (EHPSS). CPSS are reported to occur in 0.18 percent of all dogs [29], but the reported incidence varies between 1–5 percent in breeds like the Irish wolfhound and the Cairn terrier [30]–[32]. A hereditary pattern has been documented in several breeds [30][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation